Superconductivity in Mo4Ga20As with endohedral gallium clusters. (2nd June 2023) - Ruan, Bin-Bin; Chen, Le-Wei; Shi, Yun-Qing; Yi, Jun-Kun; Yang, Qing-Song; Zhou, Meng-Hu; Ma, Ming-Wei; Chen, Gen-Fu; Ren, Zhi-An
Abstract: We report the discovery and detailed investigation of superconductivity in Mo4 Ga20 As. Mo4 Ga20 As crystallizes in a space group of I 4/ m (No. 87), with the lattice parameters a = 12.86352 Å and c = 5.30031 Å. The resistivity, magnetization, and specific heat data reveal Mo4 Ga20 As to be a type-II superconductor with T c = 5.6 K. The upper and lower critical fields are estimated to be 2.78 T and 22.0 mT, respectively. In addition, electron-phonon coupling in Mo4 Ga20 As is possibly stronger than the BCS weak-coupling limit. First-principles calculations suggest the Fermi level being dominated by the Mo-4 d and Ga-4 p orbitals.